Pain, power, and anguish: the discursive structure of proportionality in the judicialization of Colombian criminal policy (2023)
Resorting to proportionality has been a canonical trend in the global constitutional model. Its narrative-structure has been used to solve the tensions between fundamental rights, by judges, from two approaches: as a legal doctrine or a sense of symmetry. This paper analyzes how both constitutional narratives of proportionality have fragmented in the judicialization of Colombian criminal policy, by mixing the content of one over the other, and how this unclear margin leaves open [malleability] analytical pores that can be appropriated by hegemonic groups. A constitutional alternative to this dilemma has involved the way to make up a uniform method of proportionality. However, it is verified from the judicialization of penitentiary policy how these monolithic narrative reforms strengthen instrumental rationality and, in turn, expands the Carceral State [its forces of power].